Gaya Komunikasi Politik Presiden Joko Widodo dalam Menyikapi Isu-Isu Kebijakan Publik Melalui Media Massa - M. Tinov; Baskoro Wicaksono (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2015)
Every president has a different style of political communication between another. Typology political communication style that uses high political communication context and low context of political communication. President SBY is one president who uses high-context communication while President Jokowi using low context communication, in which the language used is easy to understand, straightforward and not winged so as to avoid different interpretations. President Jokowi communication style in addressing issues of public policy in the mass media is not different when conducting a press conference, the